2022
DOI: 10.3389/fneur.2022.886246
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Potential Biomarkers of Regulators for M7G RNA Modification in Gliomas

Abstract: Gliomas are the most frequent primary malignant brain tumors of the central nervous system, causing significant impairment and death. There is mounting evidence that N7 methylguanosine (m7G) RNA dysmethylation plays a significant role in the development and progression of cancer. However, the expression patterns and function of the m7G RNA methylation regulator in gliomas are yet unknown. The goal of this study was to examine the expression patterns of 31 critical regulators linked with m7G RNA methylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In addition, we conducted a comprehensive risk analysis for OSCC patients with highand low-risk groups and performed independent prognostic analyses and ROC curve analyses to verify the predictive performance of OSCC prognostic risk score model. However, there are still some limitations in this study, such as the lack of further studies on the important functions and key pathways of different pathological subtypes of OSCC and m7G-related gene [43]. More experimental validation of tissue samples from patients is needed in the future to further validate our new findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, we conducted a comprehensive risk analysis for OSCC patients with highand low-risk groups and performed independent prognostic analyses and ROC curve analyses to verify the predictive performance of OSCC prognostic risk score model. However, there are still some limitations in this study, such as the lack of further studies on the important functions and key pathways of different pathological subtypes of OSCC and m7G-related gene [43]. More experimental validation of tissue samples from patients is needed in the future to further validate our new findings.…”
Section: Discussionmentioning
confidence: 97%
“…However, there are still some limitations in this study, such as the lack of further studies on the important functions and key pathways of different pathological subtypes of OSCC and m7G-related gene [ 43 ]. More experimental validation of tissue samples from patients is needed in the future to further validate our new findings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies on m7G, 34 m7G key regulatory genes were included in this study as study objects, including DCP2, AGO2, CYFIP1, CYFIP2, DCPS, EIF3D, EIF4A1, EIF4E, EIF4E1B, EIF4E2, EIF4E3, EIF4G3, GEMIN5, IFIT5, LARP1, LSM1, METTL1, NCBP1, NCBP2, NCBP2L, NCBP3, NSUN2, NUDT1, NUDT10, NUDT11, NUDT16, NUDT16L1, NUDT3, NUDT4, NUDT4B, NUDT5, NUDT7, SNUPN, and WDR4 ( Tomikawa, 2018 ; Chen et al, 2022 ). Differences in the expression patterns of these genes between patients and controls were detected using the Wilcoxon test, with a selection criterion of p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed the potential role of m7G in gliomas. Chen et al (2022) found that 17 out of 31 regulators of m7G RNA methylation showed significantly higher expression levels in gliomas. Based on these 17 genes, they developed a risk model involving three m7G methylation regulators.…”
Section: The Potential Regulatory Mechanisms Of A-to-i Rna Editing In...mentioning
confidence: 99%